1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Trapazoidal Approximation help

  1. May 2, 2010 #1
    1. The problem statement, all variables and given/known data

    [tex] \int^{5}_{1} \frac{x}{x+1} dx [/tex]

    using dx = .5

    2. Relevant equations

    [tex] \sum^{a}_{b} \frac {f(x)+f(x+dx)}{2} dx = [\frac{1}{2}f(x_{0})+f(x_{1})+\cdots+f(x_{n-1})+\frac{1}{2}f(x_{n})]dx [/tex]

    3. The attempt at a solution
    TAI = Trapazoidal Approximation Input value

    [tex] x_{0}=1 \rightarrow f(x_{0})=\frac {1}{2} \rightarrow TAI = \frac{1}{2}\frac{1}{2} =\frac{1}{4} [/tex]

    [tex] x_{1} = 1.5 \rightarrow f(x_{1}) = \frac{1.5}{2.5} \rightarrow TAI = \frac{1.5}{2.5} [/tex]

    [tex] x_{2} = 2 \rightarrow f(x_{2}) = \frac{2}{3} \rightarrow TAI = \frac{2}{3}[/tex]

    [tex] x_{3} = 2.5 \rightarrow f(x_{3})= \frac{2.5}{3.5} \rightarrow TAI = \frac {2.5}{3.5} [/tex]

    [tex] x_{4} = 3 \rightarrow f(x_{4}) = \frac{4}{5} \rightarrow TAI = \frac {4}{5} [/tex]

    [tex] x_{5} = 3.5 \rightarrow f(x_{5})= \frac{3.5}{4.5} \rightarrow TAI = \frac {3.5}{4.5} [/tex]

    [tex] x_{6} = 4 \rightarrow f(x_{6}) = \frac {4}{5} \rightarrow TAI = \frac {4}{5} [/tex]

    [tex] x_{7} = 4.5 \rightarrow f(x_{7}) = \frac{4.5}{5.5} \rightarrow TAI = \frac {4.5}{5.5} [/tex]

    [tex] x_{8} = 5 \rightarrow f(x_{8}) = \frac {5}{6} \rightarrow TAI = \frac{1}{2}\frac{5}{6} = \frac {5}{12} [/tex]

    so now, following the formula I add up all the TAI values, and the 1/2's have already been applied, so:

    [tex] \frac{1}{4} + \frac {1.5}{2.5} + \frac{2}{3} + \frac{2.5}{3.5} + \frac {3}{4}+ \frac{3.5}{4.5} + \frac {4}{5} + \frac {4.5}{5.5} + \frac {5}{12} = 5.843578644 = \frac{20248}{3465} [/tex]

    and then I multiply the sum by dx which is .5:

    [tex] \frac {20248}{3465} * \frac {1}{2} = 2.921789 [/tex]

    the book states that the answer they are looking for is 2.8968

    and for E(dx) (error) I take the second derivative:

    [tex] y = \frac {x}{x+1} [/tex]

    [tex] y' = \frac {(x+1)(1)-(x)(1)}{(x+1)^{2}} [/tex]

    [tex] y' = \frac {x+1-x}{(x+1)^{2}} [/tex]

    [tex] y' = \frac {1}{(x+1)^{2}} [/tex]

    which the same as:

    [tex] y' = (x+1)^{-2} [/tex]


    [tex] y''= -2(x+1)^{-3} [/tex]

    and the formula for error is:

    [tex] |f''(x)| \leq M [/tex] for [tex] a \leq x \leq b [/tex]


    [tex] E(dx)= \frac {b-a}{12} M (dx)^{2} [/tex]

    so now:

    [tex] |f''(1)| = .25 [/tex]

    [tex] |f''(5)| = .00926 [/tex]

    so f'' has M at 1 so to find error we do:

    [tex] \frac {5-1}{12}(.25)(.25)^{2} = \frac {1}{192} [/tex]

    the book states that the correct E(dx) is [tex] \frac {1}{48} [/tex]

    I have done this many times over and can not find where I went wrong, especially with the actually summing in the first part.
  2. jcsd
  3. May 2, 2010 #2
    For x4 you put down 4/5 instead of 3/4. You wrote the right thing in the horizontal addition, but the sum you come up with is the sum including 4/5 instead of 3/4.

    In the error part, your dx is 0.5, not 0.25.
  4. May 3, 2010 #3
    hmm i just mixed up on the post with the 4/5 instead of 3/4, thats what I have written on the paper but i just did the problem again and it all works out, i wonder why i couldnt get it to come out before.... and the error, yeah i got mixed up, thanks for the help!
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook